NuSTAR view of the Z-type neutron star low-mass X-ray binary Cygnus X-2. Issue 2 (14th November 2017) - Mondal, Aditya S; Dewangan, G C; Pahari, M; Raychaudhuri, B
Abstract: We report on the NuSTAR observation of the Z-type neutron star low-mass X-ray binary Cygnus X-2 performed on 2015 January 7. During this observation, the source exhibited a sudden decrease in count rate (dips) and stronger variability in 3–79 keV X-ray light curve. The hardness–intensity diagram shows that the source remained in the so-called normal branch of the Z-track, although an extended 'flaring branch' is observed during the dips. The source was in a soft spectral state with the 3–45 keV luminosity of L ≃ (0.5–1.1) × 10 38  erg s −1, assuming a distance of 8 kpc. Both the non-dip and dip X-ray spectra are well represented by models in which the soft band is dominated by the emission from the disc, while the hard X-ray band is dominated by the Comptonized emission from the boundary layer/corona and its reflected emission from the disc. The X-ray spectrum also revealed a broad Fe K α emission line which is nearly symmetric at the higher flux and asymmetric when the flux is reduced by a factor of ∼2. The relativistic reflection model predicts the inner radius of the accretion disc as R in ≃ 2.5–6.0  R ISCO  (≃30–73 km) for the non-dip state and R in ≃ 2.0–2.6  R ISCO  (≃24–32 km) for the dip state. If the inner disc is truncated due to the pressure arising from a magnetic field, this implies an upper limit of the magnetic field strength of ≤7.6 × 10 9  G at the magnetic poles which is consistent with other estimates.